2021
DOI: 10.1016/j.foodchem.2020.128344
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation characteristics of novel Coriolus versicolor and Lentinus edodes kombucha beverages and immunomodulatory potential of their polysaccharide extracts

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Two bands at 1654 and 1540 cm −1 were observed and were assigned to amide I and amide II vibrations of proteins. Similar observations were reported by Synytsya et al [ 100 ] for glucans from fruiting bodies of cultivated mushrooms Pleurotus ostreatus and Pleurotus eryngii . The high absorbency ranged from 1097 cm −1 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Two bands at 1654 and 1540 cm −1 were observed and were assigned to amide I and amide II vibrations of proteins. Similar observations were reported by Synytsya et al [ 100 ] for glucans from fruiting bodies of cultivated mushrooms Pleurotus ostreatus and Pleurotus eryngii . The high absorbency ranged from 1097 cm −1 .…”
Section: Resultssupporting
confidence: 91%
“…According to Baeva et al [ 102 ], the band at 890 cm −1 was attributed to (1→3)-β-D-glucans, while the bands at 850 and 929 cm −1 were characteristic of α-D-glucans, and the band at 822 cm −1 specifically to (1→3)-α-D-glucan. Synytsya et al [ 100 ] reported the bands of α-1,3-glucan at 930, 850, 822, 542, 448 and 421 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Polysaccharides with different structures and contents were detected in the mid infrared band of 800–1200 cm −1 , mainly from the C–C and C–O stretching vibrations of the glycosidic bonds and pyranose rings. In addition, it was found at 1024 cm −1 for the β-glycosidic bond and β-glucan and at 920–930cm −1 for the α-glycosidic bond [ 39 ]. According to the above two studies, CVP might have β- d -Glc p , which was similar to the structure of immune active polysaccharide β- d -glucan, suggesting that CVP had good immunomodulatory activity.…”
Section: Isolation Purification and Structural Characterization Of Cvpmentioning
confidence: 99%
“…This may be because polysaccharides are one of the immune system′s primary targets. T lymphocytes, B lymphocytes, natural killer cells, and macrophages are important immune cells, which play a crucial role in the immune system through cellular immunity [ 39 , 67 ]. As a natural polysaccharide, CVP also has the function of immune regulation.…”
Section: Bioactivities Of Cvpmentioning
confidence: 99%
“…23,24 Considering the nutritional importance of L. edodes, a number of researchers have developed value-added products from this species. For example, Sknepnek et al 25 used L. edodes to develop new kombucha products and found that the novel product contained high levels of biologically active compounds and exhibited immunomodulatory activity. A shiitake-stipe alcoholic beverage has been developed that was widely accepted by consumers.…”
Section: Introductionmentioning
confidence: 99%